Lipoma and incomplete agenesis of the corpus callosum associated with arachnoid cyst located in the temporal pole: Case report - (:unkn) unknown (My University, 2001)
This is a rare case of corpus callosum lipoma appearing with an intracranial arachnoid cyst located in the temporal pole. This case has been incidentally diagnosed by cranial computerized tomography and magnetic resonance imaging.
Keywords: Arachnoid cyst; Corpus callosum; Intracranial lipoma; Temporal pole